(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Education’s purpose is to provide an environment conducive to learning, with predictableresults. The main aim of the study is Role of principal to manage school activities and learningenvironment, in relation to humanistic and non-humanistic infrastructure. The analytic descriptivetechnique was used to conduct this study’s investigation. Through this method, a concrete image of theprincipal’s motivations for and implementation of the humanistic approach may be viewed and assessed.Finding an acceptable approach model, such as the humanistic approach, is vital for principals in orderto overcome the inadequacies of their leadership position in the execution of character educationbuilding programs.